Handbook of eudaimonic well-being - Vitterso, Joar (Springer Nature, 2016)
This handbook presents the most comprehensive account of eudaimonic well-being to date. It brings together theoretical insights and empirical updates presented by leading scholars and young researchers. The handbook examines philosophical and historical approaches to the study of happy lives and good societies, and it critically looks at conceptual controversies related to eudaimonia and well-being. It identifies the elements of happiness in a variety of areas such as emotions, health, wisdom, self-determination, internal motivation, personal growth, genetics, work, leisure, heroism, and many more. It then places eudaimonic well-being in the larger context of society, addressing social elements. The most remarkable outcome of the book is arguably its large-scale relevance, reminding us that the more we know about the good way of living, the more we are in a position to build a society that can be supportive and offer opportunities for such a way of living for all of its citizens.--Provided by publisher.